Dairy Entrepreneurship in Kandi Region of Punjab: Prospects and Constraints - Rathore, Rakesh (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out in Kandi region of Punjab, India during September, 2021 aimed to study entrepreneurial behavior and constraints faced by farmers in dairy. The entrepreneurs are key persons who promote economic growth and technological changes. The development of entrepreneurship is directly related to the socio-economic development of the society. Entrepreneurship in dairy helps farmers to increase their income or to get additional income from this important allied sector of agriculture. Total 120 farmers’ respondents were selected from four villages. The primary data were collected through pre-tested structure interview schedule. Multistage sampling was used to select respondents. The study revealed that like being own boss is important entrepreneurial behavior of overall farmers. Lack of business skills and innovativeness are important entrepreneurial behavior of marginal, small and semi-medium and large farmers respectively. Lack of business skills had highest mean score 3.77 with t-value 9.58 and p-value<.0001 which was found to be significant at 1% level of significance. Non-availability of certified veterinarian followed by lack of education and training was the important constraints faced by farmers in dairy. Innovativeness was important entrepreneurial behavior of semi-medium and large dairy farmers. There are lots of scopes for dairy entrepreneurship in Kandi region of Punjab. Proper training and education are required to the farmers mainly for marginal and small farmers for dairy entrepreneurship.